'He looks like a monster': kindergarten children, racial perceptions, and systems of socialization in dual language education - Martinez Negrette, Giselle (Race, ethnicity and education, 2024)
Dual language immersion (DLI) programs were developed in the U.S. with the expressed goal of supporting intercultural connections, bilingualism, biliteracy, and respect for diversity. However, these programs are still influenced by broader social ideas and power dynamics. From this perspective, this year-long ethnographic case study uses a sociocultural approach to examine the nature of young children's social experiences in DLI contexts. In particular, this study investigates how kindergarten children in a DLI class discern and navigate socially-constructed racial ideas. Data for this qualitative case study was collected through field notes, semi-structured interviews, and video recordings. The findings shed light on how race becomes a category that separates children and attaches particular meanings to individual subjects. This exploration helps to address antiblackness in DLI settings by analyzing how social constructions shape social practices, racial perceptions, and the socialization process in these programs.